Development of the digestive system in larvae of the Neotropical fish Prochilodus argenteus (Characiformes, Prochilodontidae) - Santos, Alcione Eneida; Pedreira, Marcelo Mattos; Santos, Thais Garcia; Moura, Guilherme de Souza; Santos, José Claudio Epaminondas dos; Silva, Robson Campos (Acta Scientiarum. Animal Sciences, 2016)
The development of the digestive system in larvae of the Neotropical fish P. argenteus was analyzed histologically. On the 3rd day after hatching, the digestive system comprised oropharyngeal cavity, esophagus and simple undifferentiated tube. Since secreting cells, positive to Alcian Blue (AB), were found in the esophagus, digestive activity in the initial phase had occurred. On the 18 and 28th days after hatching, the esophagus was positive for AB and Periodic Acid Schiff (PAS) stain. The stomach was fully differentiated, with the cardiac, fundic and pyloric regions. Different regions of the epithelium were characterized by basic and acidic secreting cells (AB and PAS positive). On the 18 and 28th days after hatching, the intestine was long, coiled and divided into proximal, middle and distal segments with pyloric ceca. Secreting cells in different regions of the gut were either positive or negative for AB and PAS. Results showed that larvae of P. argenteus exhibited digestive activity on the third day after hatching, with fully differentiated stomach and intestines on the 18 and 28th days and their different regions featuring secreting cells.